Corruption Relationship with the Values in Sila Pancasila: A Reflection of Law Enforcement - Nisa, Rahmania Fakhrun (Universitas Negeri Semarang, 2016)
This paper discusses corruption in Indonesia. Based on the cases that are still happening, corruption is one of the biggest enemies in the Indonesian state that must be fought and eradicated. There are two kinds of corruption based on the quantity, namely major corruption and minor corruption. In this paper, the problem that is the main point of thought is how or efforts to restore the values contained in the Pancasila precepts are implemented in efforts to eradicate corruption. The existence of a law that regulates cases of corruption is still considered inadequate, because there is no fear of doing so. There are three corruption eradication strategies that have been uploaded by the anti-corruption education center. Different eras for dealing with corruption cases, from the old order era to reformation. Eradication of corruption must go to the roots. Corruption usually occurs in government agencies or the bureaucracy. The people involved in corruption cases are officials, both state and private officials. Current corruption cases do not occur individually, but in well-organized and structured groups.